2014
DOI: 10.1007/s11888-014-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Deficient DNA Mismatch Repair and KRAS and BRAF V600E Mutations in Patients with Lymph-Node-Positive Colon Cancer

Abstract: While tumor stage remains the key determinant of colorectal cancer (CRC) prognosis and treatment, there is considerable stage-independent variability in clinical outcome. Molecular markers hold promise for explaining variations in clinical behavior, and may identify patient subsets with differential efficacy and survival after adjuvant chemotherapy which is standard of care for patients with lymph node-positive, i.e., stage III, colon cancer. An increased understanding of the molecular evolution and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 72 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…Compared to stage III CRCs, more stage II CRCs were with dMMR, especially the stage IIA tumors that had a higher dMMR rate of 16.6%. In our study, MMR status appeared to act as an independent prognostic biomarker for DFS in patients with stage III colon cancer that had received adjuvant FOLFOX chemotherapy a result that is consistent with other recent studies[ 6 , 23 ]. In metastatic CRC (mCRC), we found that the prevalence of dMMR was low (4.9%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to stage III CRCs, more stage II CRCs were with dMMR, especially the stage IIA tumors that had a higher dMMR rate of 16.6%. In our study, MMR status appeared to act as an independent prognostic biomarker for DFS in patients with stage III colon cancer that had received adjuvant FOLFOX chemotherapy a result that is consistent with other recent studies[ 6 , 23 ]. In metastatic CRC (mCRC), we found that the prevalence of dMMR was low (4.9%).…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have shown that CRCs with dMMRhave a better stage-adjusted survival compared with pMMR cancers. However, these data are largely from retrospective studies or focused on Lynch syndrome [ 6 , 7 , 8 ]. Molecular studies comparing CRCs with early and advanced stages have been rare.…”
Section: Introductionmentioning
confidence: 99%
“…For Stage II colon cancer, 5-year survival is reported approximately varying from 75 to 87.5 % [1,14,18] and only 3.5-5 % of these patients receive a benefit from post-surgical oncological treatments [19,20]. In addition to the traditional tumor stage, which remains the key determinant of CC prognosis and treatment, there are considerable stage-independent clinical-pathological and molecular prognostic markers identifying subsets of patients with high risk of progression and suitable for postsurgical treatment [21]. Different molecular pathways of tumorigenesis involving microsatellite (MSI) have been identified [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the traditional tumor stage, which remains the key determinant of CC prognosis and treatment, there are considerable stage-independent clinical-pathological and molecular prognostic markers identifying subsets of patients with high risk of progression and suitable for postsurgical treatment [21]. Different molecular pathways of tumorigenesis involving microsatellite (MSI) have been identified [21]. In the literature, it is reported that about 10-20 % of colorectal cancers display microsatellite instability [6-13, 19, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among patients with resected stage II and stage III CRC, MSI-H disease is associated with favourable prognosis and predicts limited benefit from adjuvant 5-fluorouracil (5-FU) monotherapy [30,31]. Additionally, approximately one-quarter of MSI-H tumours occur as a result of a germline mutation (Lynch syndrome, also known as hereditary nonpolyposis CRC) [32].…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%